The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/s1517-838246420120177
|View full text |Cite
|
Sign up to set email alerts
|

Antibiosis of Trichoderma spp strains native to northeastern Mexico against the pathogenic fungus Macrophomina phaseolina

Abstract: Sampling of agricultural soils from the Mexican northeastern region was performed to detect Trichoderma spp., genetically characterize it, and assess its potential use as a biologic control agent against Macrophomina phaseolina. M. phaseolina is a phytopathogen that attacks over 500 species of cultivated plants and causes heavy losses in the regional sorghum crop. Sampling was performed immediately after sorghum or corn harvest in an area that was approximately 170 km from the Mexico-USA border. Sixteen isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 29 publications
4
20
0
2
Order By: Relevance
“…T. harzianum (Th-7), showed certain ability that may be associated to fungistatic effects, while T. koningiopsis (Tk NRRL50190) and T. asperellum (Ta NRRL50191) showed some fungicidal effects that were captured when hyphae and sporangia of the pathogen were parasitized by Tk and Ta hyphae. Similar results have been reported for T. koningiopsis against Macrophomina phaseolina (Hernández-Mendoza et al, 2015). Osorio-Hernández et al (2011) also reported 31 Mexican Trichoderma isolates with the ability to produce volatile compounds with inhibitory properties against P. capsici.…”
Section: Discussionsupporting
confidence: 74%
“…T. harzianum (Th-7), showed certain ability that may be associated to fungistatic effects, while T. koningiopsis (Tk NRRL50190) and T. asperellum (Ta NRRL50191) showed some fungicidal effects that were captured when hyphae and sporangia of the pathogen were parasitized by Tk and Ta hyphae. Similar results have been reported for T. koningiopsis against Macrophomina phaseolina (Hernández-Mendoza et al, 2015). Osorio-Hernández et al (2011) also reported 31 Mexican Trichoderma isolates with the ability to produce volatile compounds with inhibitory properties against P. capsici.…”
Section: Discussionsupporting
confidence: 74%
“…4). After 1 week, there was some growth at 1250 mM NH 4 -N for all T. harzianum strains meanwhile the typical green centric ring indicating conidia formation at maturity [31] could be seen only in petri dishes with NH 4 -N levels from 0 to 250 mM NH 4 -N. Therefore, whereas 250 mM NH 4 -N depressed vegetative growth only, the toxicity of 1250 mM inhibited both vegetative and generative growth. Penicillium sp.…”
Section: Pgpm Tolerance To High N Concentrationsmentioning
confidence: 91%
“…The antagonists form appressory structures and tightly coil around the full extent of the hypha penetrating and degrading it [47][48][49]. This mechanism has already been demonstrated by many researchers through interactions of T. harzianum, T. viride and T. asperellum with Rhizoctonia solani, Pythium spp., Fusarium oxysporum, F. solani, S. rolfsii, S. sclerotiorum, Botrytis cinerea, Phytophthora spp., Macrophomina phaseolina, and Alternaria solani [45,[47][48][49][50][51][52].…”
Section: In Vitro Antagonistic Activity To S Sclerotiorummentioning
confidence: 99%